1983
DOI: 10.1111/j.1365-2389.1983.tb01059.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in yield between two similar sandy loam soils. I. Description of soils and measurement of yield differences

Abstract: Yields of seven different vegetable crops on one site were always much less than those on another nearby site despite the soils on both sites being of the same soil series and the incorporation of large quantities of fertilizer immediately before drilling.Severe restriction of growth on the poorer site always occurred when the plants were small. Experimental evidence showed that this restriction could not be attributed to a worse aerial environment or a poorer supply of soil nitrogen. Although there were diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…These three experiments demonstrate that it was the lack of nutrients that was invariably associated with reduced growth on Big Ground and that the lower nutrient concentrations in the plants grown on Big Ground (Costigan et al, 1983) indicated an actual deficiency of nutrients within the plants. This was in spite of the fact that the levels of broadcast fertilizer applied in the experiments were those known to produce optimum growth on Big Ground soil.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These three experiments demonstrate that it was the lack of nutrients that was invariably associated with reduced growth on Big Ground and that the lower nutrient concentrations in the plants grown on Big Ground (Costigan et al, 1983) indicated an actual deficiency of nutrients within the plants. This was in spite of the fact that the levels of broadcast fertilizer applied in the experiments were those known to produce optimum growth on Big Ground soil.…”
Section: Discussionmentioning
confidence: 94%
“…The broadcast fertilizer was incorporated into the seedbed at a rate of 190 kg ha-* N, 90 kg ha-' P and 180 kg ha-' K on both sites. This rate of fertilizer is sufficient to produce near maximum yield on Big Ground soil (Costigan et al, 1983). When banded fertilizer was applied it consisted of triple superphosphate supplying 90 kg ha-P and potassum nitrate supplying 100 kg ha-I K and 36 kg ha-'N.…”
Section: Methodsmentioning
confidence: 99%
“…One site (Big Ground, BG) had been under cultivation for approximately 10 years Longer than the other site (Plum Orchard, PO). These soils had similar chemical properties and clay mineralogies (Costigan et al, 1983). Samples of loamy sands were also taken from two sites at the Forestry Commission's Newton Nursery, near Elgin.…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%
“…However, a generalization based on soil profile properties cannot be specific enough to predict soil conditions using taxonomic classes. For example, Costigan et al (1983) [39] observed significant differences in crop yield between plots of the same soil series. The findings of this study stressed on inadequate potassium in a particular research plot.…”
Section: Introductionmentioning
confidence: 99%